2020
DOI: 10.1002/osp4.456
|View full text |Cite
|
Sign up to set email alerts
|

Group‐based trajectory modeling of body mass index and body size over the life course: A scoping review

Abstract: Background Group‐based trajectory modeling has been applied to identify distinct trajectories of growth across the life course. Objectives of this study were to describe the methodological approaches for group‐based modeling of growth across the life course and to summarize outcomes across studies. Methods A scoping review with a systematic search of Medline, EMBASE, CINAL, and Web of Science was conducted. Studies that used a group‐based procedure to identify trajectories on any statistical software were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 74 publications
5
29
0
Order By: Relevance
“…The life-course trajectories described in this study are consistent with those previously reported in the literature. Several studies have used repeated measures of BMI, waist circumference or body shape to approximate unobserved sub-groups of developmental trajectories of weight through different periods of life and estimated their association to different outcomes, including type 2 diabetes 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The life-course trajectories described in this study are consistent with those previously reported in the literature. Several studies have used repeated measures of BMI, waist circumference or body shape to approximate unobserved sub-groups of developmental trajectories of weight through different periods of life and estimated their association to different outcomes, including type 2 diabetes 31 .…”
Section: Discussionmentioning
confidence: 99%
“…One of these studies grouped BMI trajectories by sex (male and female) and age (>65, 50–65, and <50 years), resulting in six different groups of growth trajectories 28 . All studies considered sex, age, or lifestyle habits as covariates 13,15,25 . Only one study found that, although all BMI trajectories in adolescents were not significantly associated with diabetes onset, the tri‐ponderal mass index (TMI) trajectories were associated with diabetes onset 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Can different changes in the trends of BMI levels be used to estimate the risks of subsequent diabetes? Group‐based trajectory modeling approaches have become increasingly popular in recent years and have been used to determine the long‐term trajectory of BMI and its association with subsequent diabetes 11–13 …”
Section: Introductionmentioning
confidence: 99%
“…Group-based discrete trajectory mixture models were employed to develop trajectories of built environments, BMI, and waist circumference across the period of both cohorts combined. This has been used by previous studies in modelling the trajectories of BMI [ 31 ] and mental health [ 47 ]. Group-based discrete trajectory mixture models partition individuals into some groups, denoting differences in trajectory courses.…”
Section: Methodsmentioning
confidence: 99%
“…For example, while there is a legion of linking green space with health, longitudinal evidence linking green space qualities and health remains volumetrically smaller [ 27 ] and, but for some recent studies [ 28 , 29 ], rarely examines how subjective and or objective changes in those qualities may lead to changes in health status [ 30 ]. This is a widespread issue in the built environment and health literature as reported in a scoping review [ 31 ], which summarised a number of studies that measured changes (i.e., developmental trajectories) in weight status (e.g., BMI), including child and adolescent participants, but none of these studies evaluated changes in built environments as exposure of interest. This present study aimed to enrich the current literature by examining the associations between changes in a range of built environments and developmental trajectories of weight status among Australian children from age 2 to 15 years.…”
Section: Introductionmentioning
confidence: 99%